A Comparison of Motorized and Nonmotorized Scooter Injuries in Pediatric Patients Seen in US Emergency Departments. Issue 6 (4th June 2022) - Magee, Lacey C.; Chan, Calvin; Talwar, Divya; Maguire, Kathleen J.; Horn, B. David
Abstract : Objectives: We sought to characterize and compare trends in pediatric injuries sustained on motorized and nonmotorized scooters across the United States, to assess the use of safety equipment in children presenting with scooter-related injuries, and provide strategies for injury prevention. Methods: The National Electronic Injury Surveillance System was queried for motorized and nonmotorized scooter–related pediatric injuries from 2014 to 2018 in patients ages 6 to 12 years. Patient demographics, diagnosis, injury location, and narrative of the incident were collected. Bivariate and regression analyses were used to determine demographic and social associations of injury characteristics. Results: An estimated 146, 000 (11, 452 motorized and 134, 548 nonmotorized) injuries occurred in children ages 6 to 12 years over the 5 years. Three of 4 injuries occurred in children younger than 10 years, and most injuries occurred in males (56%). From 2014 to 2018, the nationwide estimated incidence of motorized scooter injuries increased by 112.1%, while that of nonmotorized scooter injuries decreased by 40.3%. Upper extremity injuries were most common with nonmotorized scooters (44.4% of all injuries), while lower extremity injuries were most common with motorized scooters (39.5% of all injuries). Head and neck injuries accounted for 27.4% of nonmotorized scooter injuries and 23.4% of motorized scooter injuries. The number of concussions in motorized scooters increased from 0.4% in 2014 to 2.7% in 2018, while concussions in nonmotorized scooters decreased from 3.5% to 2.7%. Helmets were mentioned in the medical record in 6.6% of the cases. Of these, 60.5% reported no use of helmet at the time of injury. Conclusions: From 2014 to 2018, the number of motorized scooter injuries increased by 112.1% in the pediatric population ages 6 to 12 years, whereas nonmotorized scooter injuries decreased by 40.3%. In more than 60% of the cases that mentioned a helmet, the child injured was recorded as not wearing a helmet. The rise in pediatric injuries associated with motorized scooters in contrast with the reduction of injuries associated with nonmotorized scooters highlights the need for novel public health policies and interventions promoting helmet use with motorized scooters in the pediatric population.